Cell type-specific differences in β-glucan recognition and signalling in porcine innate immune cells. Issue 1 (January 2015) - Baert, Kim; Sonck, Eva; Goddeeris, Bruno M.; Devriendt, Bert; Cox, Eric
Highlights: We explored the contribution of CR3 and dectin-1 in β-glucan recognition in pigs. As in humans, CR3 is the most important β-glucan receptor in porcine neutrophils. Macrophages utilise a more diverse receptor to recognise β-glucans. Focal adhesion kinase acts as a master switch regulating β-glucan-mediated responses. We discuss these findings in comparison with β-glucan receptors in mice and man. Abstract: β-glucans exert receptor-mediated immunomodulating activities, including oxidative burst activity and cytokine secretion. The role of the β-glucan receptors dectin-1 and complement receptor 3 (CR3) in the response of immune cells towards β-glucans is still unresolved. Dectin-1 is considered as the main β-glucan receptor in mice, while recent studies in man show that CR3 is more important in β-glucan-mediated responses. This incited us to elucidate which receptor contributes to the response of innate immune cells towards particulate β-glucans in pigs as the latter might serve as a better model for man. Our results show an important role of CR3 in β-glucan recognition, as blocking this receptor strongly reduced the phagocytosis of β-glucans and the β-glucan-induced ROS production by porcine neutrophils. Conversely, dectin-1 does not seem to play a major role in β-glucan recognition in neutrophils. However, recognition of β-glucans appeared cell type-specific as both dectin-1 and CR3 are involved in the β-glucan-mediated responses in pig macrophages. Moreover, CR3 signalling through focal adhesion kinase (FAK) was indispensable for β-glucan-mediated ROS production and cytokine production in neutrophils and macrophages, while the Syk-dependent pathway was only partly involved in these responses. We may conclude that CR3 plays a cardinal role in β-glucan signalling in porcine neutrophils, while macrophages use a more diverse receptor array to detect and respond towards β-glucans. Nonetheless, FAK acts as a master switch that regulates β-glucan-mediated responses in neutrophils as well as macrophages.